Individual differences in student consciousness during the wooden craftsmanship activity: Case study on the “Mokusho‐juku” in Miyama Ward, Kyoto prefecture - Yasunari Habara; Tsukio Toda; Naoki Awajitani; Hirotaka Kihara; Naoki Matsubara (Japan Architectural Review, 2023)
Abstract The purpose of this study is to clarify the individual differences in the consciousness of the students participating in a wooden craftsmanship activity (WCA) program. Based on a study conducted in Ono, a village located in the low uplands and mountainous region of Miyama Ward, Nantan City, in the Kyoto Prefecture, we determined the three principal components in the consciousness of the participants: “Awareness to contribution to the local region,” “Awareness to forest conservation,” and “Awareness to wooden craftsmanship.” We subsequently conducted a cluster analysis using the principal component scores of the university students participating in the study and categorized them into the following four groups: “Contribution to the local region group,” “Design‐oriented group,” “Moderate group,” and “Environment conservation group,” to clarify the effects of the activity and the important themes related to design education and WCA programs.